Lack of public participation and good governance, who is fooling who? - Ragolane, M.; Malatji, T. L. (Technium Social Sciences Journal, 2021)
This empirical paper sought to determine the lack of public participation and good governance, and to understand who is turning the blind eye on the issue. Local government municipalities have the obligation to exercise good governance, this is to ensure that there is quality service delivery and engagements between the municipalities becomes greater. Therefore, the municipalities are therefore responsible to establish the criterion for participation, transparency, adherence to the rule of law, effectiveness, equity, responsibility, accountability, and consistency. However, in the local government all these important aspects of good governance are neglected and avoided. The question of who is fooling who? Is basically an intention to point out that the idea of good governance does not have a single side but the public, the organisations and the state are included? For the good governance and the democracy of participation there must be an increase in the quality of feedback and the processes of policy formulation, and most importantly with the prevalence of participation. In the south African local government, municipalities have diluted the importance of public participation and that has caused the growing corruption scandals, protests, low service delivery and failing governments.